INOVASI PENDIDIKAN MELALUI PENGEMBANGAN KURIKULUM DI SMA SCIENCE PLUS BAITUL QUR’AN SRAGEN - Rifa’i, Hamzah Yusuf; Nurkhasnah, Siti; Nur Hasanah, Mudzakaroh; Asmawi, Muhammad Nurul Ihsan; Puspitasari, Dila Oktariani; Zaman, Badrus (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
The purpose of this study was to explore the curriculum innovation implemented in SMA Science Plus Baitul Qur'an Sragen. The method used in this study is a qualitative descriptive method with data collection through observation, literature study, and documentation. The data analysis technique used is comparative logic analysis which includes data reduction, data presentation, and drawing conclusions. The curriculum used integrates the character-based National Curriculum and the Science Plus Baitul Qur'an Curriculum, which includes tahfidz programs, Turats book studies, and foreign language learning. These programs are carried out both inside and outside the classroom. The results of the study indicate that curriculum development is carried out systematically through needs analysis and continuous evaluation. Challenges faced by researchers include time constraints, limited relevant literature, and adjustments to student characteristics. However, through effective collaboration, the curriculum was successfully developed and implemented.